Modulation of affinity of a marine pseudomonad for toluene and benzene by hydrocarbon exposure - Law, A.T.; Button, D.K. (1986)
Trace (microgram liter-1) quantities of either toluene or benzene injected into an amino-acid limited continuous culture of Pseudomonas sp. strain T2 were utilized immediately with affinities of 2.6 and 6.8 liters g of cells-1 h-1, respectively, and yielded large amounts of organic products, carbon dioxide, and cells. The immediate utilization of hydrocarbons by hydrocarbon-deprived organisms helps to establish the nutritional value of nonpolar substrates in the environment. The observation of small Michaelis constants for toluene transport led to tests of metabolic competition between hydrocarbons; however, competitive inhibition of toluene metabolism was not found for benzene, naphtalene, xylene, dodecane, or amino acids. Benzene and terpenes were inhibitory at milligram liter-1 concentrations. Toluene was metabolized by a strongly inducible system when compared with benzene. The capacity of toluene to effect larger affinity values increased with exposure time and concentration. The kinetics of induction suggested saturation phenomena, resulting in an induction constant, K(ind), of 96 μg of toluene liter-1. Maximal induction of amino-acid-grown cells required about 80 h, with the affinity reaching 317 liters g of cells-1 h-1.